PENGEMBANGAN DAN IMPLEMENTASI SISTEM ABSENSI DI SMAN 7 BOGOR BERBASIS WEB - Al-Ikhsan, Safaruddin Hidayat; Jaenudin, Jejen; Ardiansyah, Dicky (Krea-TIF: Jurnal Teknik Informatika, 2014)
Attendance on hours worked is the duty of every employee in an agency or company, ranging from the lowest level to the highest level. Similarly, the school, the presence of teachers, staff and students to be an important indicator for the sake of the implementation process of a good education. If the number of teachers, employees and students are not many, of course, can be observed directly. However, if the polynomial would be difficult to monitor manually. SMAN 7 Bogor as one of the organizers of education, has a number of teachers, staff, and students are many. In order for the process of education can work well, we need a system that can control these activities. Based on the design of a system that has been done before, so in this research and their attendance system development field implementation. The development of this system adopts the Waterfall method, with the stages of analysis, design, implementation, testing, and maintenance. Analysis and design has been done before, so in this study implementation, testing, and maintenance. Implementation is done using a web-based system. Based on the method of Black Box testing, functional system can run well be absent, among which are: 1) input, edit, and delete data student / teacher; 2) create a new class, edit, or delete it; 3) Input pain, license, truancy; 4) Presence manual input; 5) recap print absent teachers; 6) absences per class recap print; and 7) Print recap absent per student. This system has been implemented in schools and running properly.